The Fragile Peace 1919-39 - Reader's Digest (U.S.A Reader's Digest, 1996)
A lively chronicle of world history between the two world wars examines the political, economic, social, and cultural factors that transformed the world; assesses the influence of such pivotal events as the Great Depression; analyzes innovations in the world of art and music; and explores the growth of new forms of popular entertainment.